Energy and Nitrogen Retention of Bali Heifers (Bos sondaicus) Fed Diet Containing Different Energy Protein Level - Ni Nyoman Suryani; I Wayan Suarna; I Gede Mahardika; Ni Putu Sarini; Lindawati Doloksaribu (TERNAK TROPIKA Journal of Tropical Animal Production, 2020)
Database of Bali heifer particularly on their nutrient digestibility, energy and nitrogen balance of various ration formulas on their growth performance were limited.  A randomized block design with four types rations of metabolizable energy (ME) and crude protein ratios, i.e. of 2,045.38 kcal ME/kg:12.06% (Treatment A), 2,103.57 kcal ME/kg:13.11% (Treatment B), 2,201.85 kcal ME/kg:13.97% (Treatment C) and 2297.60 kcal ME/kg:15.05% (Treatment D) were conducted to evaluate nutrient digestibility, energy and nitrogen retention of Bali heifers.  The rations consisted of concentrate, urea, molasses, king grass, coconut oil and vitamin-mineral mix.  Results showed that Treatment D improved significantly of the 7,814.34 kcal/d digestible energy, 49.87 g/d digestible nitrogen, 11,015.06 kcal/d energy intake, 423.53 g/d nitrogen intake, 67.76 kcal/d energy retention, 7.91 g/d nitrogen retention, 0.33 kg/d daily weight gain (ADG), (P<0.05).  In summary, ration for Bali heifer should contain at least 2,297.60 kcal ME/kg:15.05% crude protein for better average daily weight gain.